Changing Demographic Structure of Nepal: from Youth Bulge to Aging Society - Rawat, Tara Keshar (Journal of Contemporary Review, 2024)
This study documents Nepal’s transition from a youth-bulge population structure toward a progressively ageing society by analysing census age- composition data (1991, 2001, 2011, 2021) together with trends in crude birth and death rates and life expectancy. The purpose of this study is to describe changes in Nepal’s age composition, quantify trends in crude birth rate (CBR), crude death rate (CDR) and life expectancy at birth, and discuss policy implications for realizing a demographic dividend and preparing for population ageing. This study is primarily based on secondary sources of data and descriptive research method. Data sources are used from Central Bureau of Statistics, National population and housing census thematic Reports-X; Ageing Situation in Nepal, thematic reports-IX; Mortality in Nepal, World Bank/FRED series). Using published tabulations from Nepal’s national censuses this paper documents the share of children (0–14) fell markedly while the share of older persons (60+) rose, crude birth rates declined substantially, crude death rates declined more slowly, and life expectancy increased. These shifts indicate that Nepal is passing through the demographic transition: a falling fertility regime and rising survival have created an expanded working-age population now and a growing older population to plan for in the near future.